ByzRev 06.2024.007: Richard Evans – Shaun Tougher (eds), Generalship in Ancient Greece, Rome and Byzantium.: Edinburgh: Edinburgh University Press 2022. - Wild, Jonathan (The Byzantine Review, 2024)
Richard Evans – Shaun Tougher (eds), Generalship in Ancient Greece, Rome and Byzantium. Edinburgh: Edinburgh University Press 2022. 376 pp. – ISBN 978-1-4744-5996-9